2017
DOI: 10.1159/000478852
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of “Positive” Behaviours in Primary Progressive Aphasias

Abstract: Background/Aims: Although some patients with primary progressive aphasia (PPA) exhibit novel or improved skills after the onset of dementia, these changes have yet to be quantified. Therefore, this study systematically explored and identified the emergence of positive behaviours after dementia onset. Methods: This study included 48 carers of patients with PPA: 12 nonfluent/agrammatic PPA (nfvPPA), 22 semantic variant PPA (svPPA), and 14 logopenic variant PPA (lvPPA). The presence and frequency of positive beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Although singing and dancing are important musical activities, some patients in our cohort displayed increased singing or dancing without an increased interest in music. None of our PNFA patients showed musicophilia, which is in line with previous studies 12,28 . We further found that sound aversion was not always associated with music aversion and vice versa.…”
Section: Discussionsupporting
confidence: 93%
“…Although singing and dancing are important musical activities, some patients in our cohort displayed increased singing or dancing without an increased interest in music. None of our PNFA patients showed musicophilia, which is in line with previous studies 12,28 . We further found that sound aversion was not always associated with music aversion and vice versa.…”
Section: Discussionsupporting
confidence: 93%
“…Symptoms such as absent or misplaced empathy, social disinhibition and faux pas, a more fatuous sense of humour and pathological sweet tooth are common in both svPPA and behavioural variant frontotemporal dementia [ 29 , 53 57 ]. Within this spectrum, certain behavioural features, such as food faddism, exaggerated reactions to pain and ambient temperature, behavioural rigidity with clock-watching and obsessional interest in numbers, puzzles (especially Sudoku and jigsaws) and music (‘musicophilia’) seem particularly linked to svPPA [ 30 , 53 , 58 60 ]. A unifying theme here may be impaired understanding of emotional and somatic signals due to both deficient and over-generalised responses to sensory information [ 41 , 42 , 55 , 56 , 61 ], analogous to recognition failures and ‘regularisation errors’ in other cognitive domains.…”
Section: Canonical Syndromes Of Primary Progressive Aphasia: Semanticmentioning
confidence: 99%
“…Symptoms such as absent or misplaced empathy, social disinhibition and faux pas, a more fatuous sense of humour and pathological sweet tooth are common in both svPPA and behavioural variant frontotemporal dementia [29,[53][54][55][56][57]. Within this spectrum, certain behavioural features, such as food faddism, exaggerated reactions to pain and ambient temperature, behavioural rigidity with clock-watching and obsessional interest in numbers, puzzles (especially Sudoku and jigsaws) and music ('musicophilia') seem particularly linked to svPPA [30,53,[58][59][60]. A unifying theme here may be impaired understanding of emotional and somatic signals due to both deficient and over-generalised responses to sensory information [41,42,55,56,61], analogous to recognition failures and 'regularisation errors' in other cognitive domains.…”
Section: Key Associationsmentioning
confidence: 99%